P17. Dose map variations over time of a blood irradiator. (September 2016) - Trauernicht, C.; Johnson, C.; Mason, B.
Abstract : Introduction: The Mølsgaard Gammacell 2000 blood irradiator contains a Cs-137 source encapsulated in a stainless steel tube. The beaker containing the blood bag rotates during irradiation to give a uniform dose to the blood. Dose mapping is done to ensure that the given radiation dose to the blood is within the specified limits of minimum 25 Gy and maximum of 50 Gy to prevent graft versus host disease in bone marrow transplant patients. Materials and methods: Dose map records exist for most years from 2005 to 2016, with the exception of 2006 and 2007. Until 2011 the dose maps were done using MOSFET detectors, with the detectors fitted in a custom tissue-equivalent phantom. Since 2012 the dose mapping was done using a type of gafchromic film in a cylindrical tissue-equivalent phantom. In addition, in 2013, dose mapping was also done using TLDs. Results: In 2005 the dose map was fairly uniform and flat. The 2008 map is starting to show a very subtle dip, which becomes more pronounced in 2009 and has remained since. Minimum doses remain greater than 25 Gy. Conclusion: The dose map dip that has become evident may be a sign of the source settling in its encapsulation. Annual checking of the dose map is very important for a blood irradiator. Changes of the dose distribution with time may result in a minimum dose of less than the recommended 25 Gy, which would require an increase in the irradiation time.